MICROBIOLOGICAL MONITORING IN THE DEPARTMENTS OF THE PERINATAL CENTER - Елена Витальевна Наумкина; Елена Владимировна Пахалкова; Татьяна Вячеславовна Пядочкина; Ольга Андреевна Абросимова (The Publishing House Medicine and Enlightenment, 2018)
Purpose of the study - analysis of the results of microbiological monitoring in obstetric departments and the neonatal resuscitation department of the second stage of nursing. Materials and methods. From 2014 to 2016, 7985 samples of biomaterial from patients from obstetric departments of the CCPC and 1578 samples from the newborn in resuscitation departments of the second stage of nursing were examined microbiologically. Results. The dominance of opportunistic microorganisms in samples of biomaterial from patients of the obstetric physiological department is noted; in comparison with the results of the survey of patients of the observatory department, the markers of antibiotic resistance in the isolated strains are found much more often. In newborns of the intensive care unit of the second stage of nursing, pathogens with relatively low potential pathogenicity predominate- mainly coagulase-negative staphylococci and enterococci. Conclusion. Qualitative and quantitative features of pathogens colonizing various loci in the studied categories of patients require revision of the algorithms for conducting from the standpoint of the effectiveness of antibiotic therapy and preventing the development of antibiotic resistance.